2014
DOI: 10.1007/s12010-014-1365-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Production of Microalgae and Removal of Nutrient Using a Microalgae Membrane Bioreactor (MMBR)

Abstract: In present research, a microalgae membrane bioreactor (MMBR) was constructed by combining the optical panel photobioreactor (OPPBR) and membrane bioreactor (MBR). Experiments were conducted in MMBR pilot-plant configuration for 150 days. A biomass productivity of 2.53 g/l/day with light transmittance of 94 % at a 300-mm depth in the OPPBR was achieved. The total reduction of chemical oxygen demand (COD) and biochemical oxygen demand (BOD) in the MMBR were found to be 96.99 and 97.09 %, respectively. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…In st to MRT of 3 days, the lowest microalgae productivity occurred at 1.5 days because of erly high F/M ratios. In addition, light may limit the microalgal growth due to self-shading h biomass concentration; therefore, dark respiration of algae occurs in MPBR [17]. This ot proved in this study.…”
Section: Figure 2 Demonstrates That the Variation Of Chlorella Vulgarsupporting
confidence: 69%
See 1 more Smart Citation
“…In st to MRT of 3 days, the lowest microalgae productivity occurred at 1.5 days because of erly high F/M ratios. In addition, light may limit the microalgal growth due to self-shading h biomass concentration; therefore, dark respiration of algae occurs in MPBR [17]. This ot proved in this study.…”
Section: Figure 2 Demonstrates That the Variation Of Chlorella Vulgarsupporting
confidence: 69%
“…Moreover, the S/V ratio was smaller than the ratio in previous studies by Gao, et al [13,18]; nevertheless, the higher production was achieved in this study due to the lower biomass concentration ( Table 1). The high concentration of algae could cause the respiration in the dark [17] and the smaller production in these studies.…”
Section: Figure 2 Demonstrates That the Variation Of Chlorella Vulgarmentioning
confidence: 73%
“…Other studies suggested that nutrients was separated from the wastewater containing colored substances by using coagulants, flocculants, and adsorbents and then added to the microalgae culture medium [30,35,[41][42]. In previous studies on low-strength wastewater treatment using microalgal cells, concentrations of total nitrogen (TN) and total phosphorus (TP) were 25.4-53.2 mg/L and 1.2-12.2 mg/L, respectively [15,23,[45][46][47]. A few studies have dealt with microalgae cultivation as a strategy for treating anaerobically-digested piggery wastewater [4,36].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the microalgal biomass can be used to produce biofuel, fertilizer, etc. (Choi, 2015;Gao et al, 2014Gao et al, , 2015.…”
Section: The Effect Of Hrt On Mpbr Performancementioning
confidence: 99%